Dry fractionation of lentils by air classification - Composition, interfacial properties and behavior in concentrated O/W emulsions. (15th January 2022) - Funke, Matthias; Boom, Remko; Weiss, Jochen
Abstract: Dry fractionation has shown to be a promising method to obtain less refined protein ingredients from legumes with novel technofunctionalities compared to solvent extracted protein isolates. However, the relationship between composition and functionality of such fractions especially for use as emulsifiers in concentrated emulsions is still unclear. In this study, investigations were carried out with a variety of lentil fractions having different protein contents, on their ability to emulsify and stabilize concentrated oil-in-water emulsions. Fractions produced by dry fractionation had protein, starch, and fiber contents of 11–54%, 0–58% and 19–32%, respectively, and median particle sizes of samples varied between 6 and 78 μm. Protein solubility and zeta potential varied little, and concentrated oil-in-water emulsions prepared with these different fractions at similar protein contents had similar oil droplet sizes. In contrast, the bulk rheology differed markedly with emulsions exhibiting a more solid like behavior when formed with less-refined fractions. Similarly, differences in the development of interfacial rheology were found. These effects were attributed to differences in the amount and size of non-protein particles, which are entrapped in the droplet network and interact with the interfacial layer, highlighting the importance of the presence of such compounds. Highlights: Dry fractionation is a sustainable method to alter the composition of lentil flour. Dry fractionated lentil fractions can stabilize concentrated oil-in-water emulsions. The degree of refinement has impact on microstructure and functionality. Non-protein components of lentils contribute to functional properties.